2023
DOI: 10.18063/esp.v8.i1.1513
|View full text |Cite
|
Sign up to set email alerts
|

Turkish validation of the Psy-Flex Scale and its association with resilience and social support

Abstract: Psychological flexibility is an important psychological factor influencing various individual and relational outcomes. However, there is a scarcity of evidence about cross-culturally validated measures available. The aim of the present study was to assess the Turkish validation of the Psy-Flex Scale, which is a new and recently developed measure of this construct and test its relationship with resilience and social support. The sample comprised 516 adults (52.3% males) with an age range of 18–60 years (M = 27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The and mental health (e.g., Tavakoli et al, 2019). These results support the validity of the instrument in measuring psychological flexibility, and they are similar to those of the original research on the instrument (Gloster et al, 2021) and adaptations (Jo et al, 2023;Yıldırım & Aziz, 2023). This study reinforces Psy-Flex as a valid and pragmatic instrument for measuring psychological flexibility.…”
Section: Convergent Validitysupporting
confidence: 86%
“…The and mental health (e.g., Tavakoli et al, 2019). These results support the validity of the instrument in measuring psychological flexibility, and they are similar to those of the original research on the instrument (Gloster et al, 2021) and adaptations (Jo et al, 2023;Yıldırım & Aziz, 2023). This study reinforces Psy-Flex as a valid and pragmatic instrument for measuring psychological flexibility.…”
Section: Convergent Validitysupporting
confidence: 86%
“…The majority of the personal factors reported have already been identified in previous studies as protective factors of resilience (Yildirim & Aziz, 2023). However, it is worth noting that most teachers reported that their love for the profession and the children, the feeling they provide through their work, and the belief that they can help improve their students' quality of life provide motivation to continue despite the difficulties.…”
Section: Journal Of School and Educational Psychologymentioning
confidence: 93%
“…This unidimensional scale consists of six items, and participants rate each item on a 5-point Likert scale, ranging from 1 (very seldom) to 5 (very often). The Turkish validation of the scale was conducted by Yildirim and Aziz (2023), who provided strong evidence regarding the validity (i.e., construct validity) and reliability (i.e., internal consistency reliability) of the scale in the Turkish context. To calculate the total score, all item responses are summed, with higher scores indicating a higher level of psychological flexibility.…”
Section: Methodsmentioning
confidence: 99%